ANALISIS GOOD CORPORATE GOVERNANCE DAN KINERJA KARYAWAN DALAM PENGHIMPUNAN DANA LAZISMU SIDOARJO - Achmad, Fadelia; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2022)
The purpose of this study is to see the implementation of Good Corporate Governance by applying 5 principles, and the principles are transparency, accountability, responsibility, independence, and fairness, and also the performance of employees at the amil zakat institution on fundraising of funds obtained by the amil zakat institution. This study uses a qualitative phenomenological method using purposive sampling technique and in collecting data using interview and observation techniques. In this study, there were 3 sources as a reference for interview data, they are the Chairman of the Governing Body, Head of the Office, and Muzakki Lazismu Sidoarjo. The results of this study showed that the implementation of good corporate governance and employee performance has been implemented properly and correctly, which can be seen from the effective and efficient institutional performance system as well as the high achievement of targets made by Lazismu Sidoarjo employees, but due to a pandemic Covid 19 has caused the collection of funds at Lazismu Sidoarjo to experience a significant decline.